2004
DOI: 10.1152/ajpheart.00852.2003
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of cardiovascular ghrelin receptor occurs in the hyperdynamic phase of sepsis

Abstract: Ghrelin, a newly identified endogenous ligand for growth hormone secretagogue receptor 1a (GHSR-1a, i.e., ghrelin receptor), was recently demonstrated to be a potent vasoactive peptide. Although sepsis is characterized by an early, hyperdynamic phase, it remains unknown whether ghrelin or GHSR-1a plays a role in the cardiovascular response to sepsis. To determine this, polymicrobial sepsis was induced by cecal ligation and puncture in male adult rats. At 5 h (i.e., early sepsis) or 20 h (i.e., late sepsis) aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 45 publications
1
46
1
1
Order By: Relevance
“…Similar to CLP alone animals (19), serum levels of ghrelin in RCI animals decreased to 87 ± 20 pg/mL (P < 0.05), representing a 35% reduction at 20 h after RCI (68 h after irradiation or 20 h after CLP). And ghrelin gene expression in the stomach (the major source of ghrelin in the circulation [11]) was decreased by 87% at 20 h after RCI (P < 0.05, Figure 1B).…”
Section: Ghrelin Levels Decrease After Rcimentioning
confidence: 73%
See 1 more Smart Citation
“…Similar to CLP alone animals (19), serum levels of ghrelin in RCI animals decreased to 87 ± 20 pg/mL (P < 0.05), representing a 35% reduction at 20 h after RCI (68 h after irradiation or 20 h after CLP). And ghrelin gene expression in the stomach (the major source of ghrelin in the circulation [11]) was decreased by 87% at 20 h after RCI (P < 0.05, Figure 1B).…”
Section: Ghrelin Levels Decrease After Rcimentioning
confidence: 73%
“…It has been linked to the regulation of pituitary hormone secretion, feeding, energy homeostasis, gastrointestinal function, cardiovascular system, and immune system (16)(17)(18). Our recent studies have shown that circulating levels of ghrelin decreased significantly in a rat model of polymicrobial sepsis induced by cecal ligation and puncture (CLP), and ghrelin administration decreases inflammatory responses, improves organ blood flow, attenuates tissue injury, and reduces mortality under such conditions (18)(19)(20)(21). However, it remains unknown whether ghrelin ameliorates sepsis-induced organ injury and mortality after radiation exposure.…”
Section: Introductionmentioning
confidence: 99%
“…GHS-R expression is up-regulated in left ventricular tissue from patients with congestive heart failure [3] and atherosclerosis [8], as well as in the hearts of rats during the hyperdynamic phase of sepsis [28]. These results indicate that GHS-R signaling is altered in cardiovascular disease, and point toward the use of ghrelin in pharmacologic therapy of heart disease.…”
Section: Introductionmentioning
confidence: 88%
“…In rodents, ghrelin attenuated endotoxin-induced anorexia, reduced cytokine production, and improved mortality associated with lipopolysaccharide (LPS)-induced endotoxic shock (43)(44)(45). In a well-designed series of studies, Dixit et al showed that ghrelin and the GHS-R are found in human T cells and monocytes, where ghrelin specifically inhibited the chronic synthesis of pro-inflammatory anorectic cytokines such as leptin, interleukin 1ß (IL-1ß), IL-6, and tumor necrosis factor · (46).…”
Section: Ghrelin and Metabolismmentioning
confidence: 99%